Gender alternation and horizontal parity in the democracy of political organizations: a systematic review under the sdg approach - Alegria Angulo, Jhon Sander (2025)
Objective: The main objective of the research work was to analyze the status of gender alternation and horizontal parity in the democracy of political organizations under the approach of Sustainable Development Goal 5.Theoretical Framework: The study raises the need tocarry out more detailed research to better understand compliance with the norms that support gender alternation and horizontal parity in political organizations, with the aim of promoting more equitable and democratic participation in decision-making.Method: The approach of the study was qualitative with a systematic review design, population and sample made up of 20 scientific articles indexed in databases such as SCOPUS, SCIELO, DOAJ and others, with the entry of the phrases "Participation" and "process" and "woman", and "Gender alternation", "Horizontal parity" being relevant.Results and Discussion: After the review and analysis, it was identified that the situation of alternation of gender and horizontal parity has a low index, ranging between 7.4% and 50.64%. In contrast, male participation varies between 48.32% and 94%. In addition, the factors that predominate in the alternation of gender and horizontal parity in democracy are political, social, economic and cultural.Research Implications: It isconcluded, therefore, that gender alternation is not adequately complied with, and a detailed study is necessary to determine the reality of compliance with the rules that guarantee gender alternation and horizontal parity.Originality/Value: The study addresses gender alternation and horizontal parity in the democracy of political organizations from a multidimensional perspective, considering political, social, economic and cultural factors. This comprehensive approach allows for a more complete understanding of the challenges and barriers to gender equity in political participation.